2013
DOI: 10.4236/ojst.2013.36055
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Anomalies in Norwegian School Children

Abstract: Introduction: Dental anomalies have been widely examined, but no such studies have been conducted in Norway. The purpose of this study was to examine the prevalence of dental anomalies and investigate their possible association with gender and dental occlusion. Methods: Panoramic radiographs and study models of 500, 12-year-old school children (273 girls, 227 boys) were analyzed for the presence of dental anomalies including agenesis, taurodontism, pulp stones, microdontia, macrodontia, impaction, short roots,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
3
14
0
2
Order By: Relevance
“…In other part of the world, prevalence of impaction has been reported at 3.74% in Indian population 37 and 8.4% in Norwegian population. 38 In similar studies done on non-orthodontic population, prevalence has been found to be 8.3% and 9.9% by Ezoddini et al 4 & Thongudomporn and Freer 39 respectively.…”
Section: Discussionmentioning
confidence: 78%
“…In other part of the world, prevalence of impaction has been reported at 3.74% in Indian population 37 and 8.4% in Norwegian population. 38 In similar studies done on non-orthodontic population, prevalence has been found to be 8.3% and 9.9% by Ezoddini et al 4 & Thongudomporn and Freer 39 respectively.…”
Section: Discussionmentioning
confidence: 78%
“…Its prevalence varies between countries and tribes. For example congenitally missing teeth is the most prevalent dental anomaly found in Indians [ 1 , 2 ], Saudi Arabians [ 3 ], Turkish [ 4 ] and Norwegian children [ 5 ]. In Nigeria however, enamel hypoplasia is the most common dental anomaly in children while hypodontia is a rare clinical feature [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted within the past 6 years, the prevalence ranged from 4.74 to 45.1%. [ 4 7 8 9 10 11 12 13 ] These variations are most likely due to the sampling technique, subject's inclusion criteria, and the study design. Unlike other researches which assessed the radiographs and dental records alone, this study was supplemented by the subjects’ study cast.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated 28.4% subjects with at least a single anomaly, at a very close range with the Norway and Iran population, at 28.2 and 29%, respectively. [ 10 11 ] However, both studies included those in mixed dentition. Uslu et al .…”
Section: Discussionmentioning
confidence: 99%